Implementasi Keperawatan Terapi Spiritual Pada Pasien Skizofrenia dengan Masalah Keperawatan Perilaku Kekerasan - Sri Martini; Sri Endriyani; Natasyah Dwi Putri Hadita (NHM PRESS, 2022)
Violent behavior is a response to a stressors faced by someone, which is shown by commiting violent both on oneself, others and the environment, verbally and non-verbally, aiming to hurt others physically and shysichologically, which is indicted by actual behavior violent. To overcome the recurrence the patients needs to get treatment, namely the implementation of the implementation strategy. This type of research is descriptive in the form a case study to explore the implementation of spiritual healing nursing in schizophrenic patients with behavior problems at Ernaldi Bahar Hospital in the Province of South Sumatera. The research subjects to be studied were two patients, schizophrenic with The instruments used in this scientific paper are assessment sheets and data from medical records. The resuts of the study show that the patients is able to control violent behavior by the implementation of the 1 spiritual healing strategies